Method for improving adhesive strength of resin molded products to adhesives and composite with improved adhesive strength
By adding an amorphous resin to the resin composition of the liquid crystal polymer resin product and adjusting the proportion of each component, the problem that the liquid crystal polymer resin product in the prior art is difficult to improve the bonding strength while maintaining mechanical strength, and a more efficient bonding effect in the manufacturing of electronic components is achieved.
Patent Information
- Application Number
- JP2020180648
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-28
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2040-10-28
AI Technical Summary
The prior art is difficult to improve the adhesive strength with the adhesive while maintaining the mechanical strength of the liquid crystal polymer resin product. Especially in the manufacturing process of electronic components, it is necessary to reduce the amount of adhesive used while increasing the adhesive strength to resist shock and vibration due to the miniaturization of the electronic components.
By adding an amorphous resin to the resin composition of the liquid crystal polymer resin product, and adjusting the ratio of the liquid crystal polymer resin, amorphous resin and mineral filler, it is ensured that the content of the liquid crystal polymer resin is between 50 and 99 parts mass, the content of the amorphous resin is between 1 and 50 parts mass, and the content of the mineral filler is between 0.1 and 120 parts mass.
It is achieved to improve the adhesive strength with the adhesive without reducing the mechanical strength of the liquid crystal polymer resin product, and is suitable for electronic components and other fields.
Smart Images

Figure 0007661023000001 
Figure 0007661023000002 
Figure 0007661023000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for improving the adhesive strength of a resin molded article made of a resin composition containing a liquid crystal polymer resin and an inorganic filler to an adhesive, and also to a composite having improved adhesive strength, which is formed by bonding a resin molded article to another member with an adhesive. [Background technology]
[0002] A resin molded product made of a liquid crystal polymer resin composition is used by bonding it to other members with an adhesive, but since the adhesive strength of the liquid crystal polymer resin itself is low, there is a risk of peeling off at the adhesive portion. Therefore, in the past, in Patent Documents 1 to 3, a method has been used in which a large amount of filler such as glass fiber or talc is added to the resin composition to roughen the surface of the resin molded product, thereby increasing the apparent adhesive area, or generating an anchor effect of the filler itself, thereby improving the adhesive strength. However, such a method deteriorates the appearance of the resin molded product, so that the applicable uses are limited.
[0003] In addition, Patent Documents 4 to 7 propose a method of adding an epoxy group-containing copolymer to improve adhesive strength while suppressing deterioration of appearance and dust generation. However, since improving adhesive strength leads to a decrease in mechanical strength at the same time, the amount of the copolymer added cannot be increased, and the effect of improving adhesive strength is limited.
[0004] On the other hand, Patent Documents 8 to 11 disclose improving the fluidity and moldability of a resin composition containing a liquid crystal polymer resin and a polyarylate, but do not disclose anything about improving the adhesive strength when a resin molded product is joined to another component using an adhesive. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6416442 [Patent Document 2] Patent No. 5541330 [Patent Document 3] Patent No. 5136324 [Patent Document 4] Patent No. 6545416 [Patent Document 5] Patent No. 6037709 [Patent Document 6] JP 2011-137064 A [Patent Document 7] JP 2019-73591 A [Patent Document 8] Japanese Patent Application Publication No. 5-5054 [Patent Document 9] Patent No. 4135064 [Patent Document 10] JP 2004-315776 A [Patent Document 11] JP 2010-83930 A Summary of the Invention [Problem to be solved by the invention]
[0006] Due to their excellent fluidity and dimensional stability, liquid crystal polymer resin compositions are used as components of electronic parts in mobile devices such as smartphones, tablets, and notebook PCs, as well as electronic parts for vehicles. In the manufacturing process of these devices, resin molded products made of liquid crystal polymer resin compositions are often bonded to other parts with an adhesive. In recent years, due to miniaturization of electronic components, it has become necessary to reduce the application area of adhesives, and therefore, improvement of adhesive strength is required between resin molded products and adhesives. On the other hand, in mobile devices and cars, strong impacts and vibrations are applied in the usage environment, and there is a risk of damage to the parts during use, so it is necessary to avoid a decrease in the mechanical strength of the resin molded product itself. In other words, there is a demand for a method for improving the adhesive strength between a resin molded product and an adhesive while maintaining the mechanical strength of the resin molded product made of a liquid crystal polymer resin composition.
[0007] Therefore, an object of the present invention is to provide a method for improving the adhesive strength of a resin molded article to an adhesive without impairing the mechanical strength of the resin molded article. Another object of the present invention is to provide a composite body having improved adhesive strength, which is formed by bonding a resin molded article to another member with an adhesive. [Means for solving the problem]
[0008] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by further blending an amorphous resin into a resin molded product made of a resin composition containing a liquid crystal polymer resin and an inorganic filler, and adjusting the blending amounts of the liquid crystal polymer resin, the amorphous resin, and the inorganic filler. The present invention has been completed based on this finding.
[0009] That is, according to one aspect of the present invention, A method for improving adhesive strength to an adhesive of a resin molded product made of a resin composition containing a liquid crystal polymer resin and an inorganic filler, comprising: The resin composition is further blended with an amorphous resin, The adhesive strength improving method is characterized by adjusting the amount of the liquid crystal polymer resin to 50 parts by mass or more and 99 parts by mass or less, the amount of the amorphous resin to 1 part by mass or more and 50 parts by mass or less, and the amount of the inorganic filler to 0.1 parts by mass or more and 120 parts by mass or less, relative to a total of 100 parts by mass of the liquid crystal polymer resin and the amorphous resin.
[0010] In one embodiment of the present invention, it is preferable to adjust the blending amount of the liquid crystal polymer resin to 70 parts by mass or more and 99 parts by mass or less, and the blending amount of the amorphous resin to 1 part by mass or more and 30 parts by mass or less.
[0011] In an embodiment of the present invention, the amorphous resin is preferably at least one selected from the group consisting of polyarylate, polyethersulfone, polysulfone, polyphenyl ether, and polycarbonate.
[0012] In a preferred embodiment of the present invention, the amorphous resin is at least one selected from the group consisting of polyarylates and polysulfones.
[0013] In an embodiment of the present invention, it is preferable that the resin composition further contains 1 part by mass or more and 5 parts by mass or less of an epoxy group-containing copolymer per 100 parts by mass of the liquid crystal polymer resin and the amorphous resin in total.
[0014] In an embodiment of the present invention, the liquid crystal polymer resin comprises the following structural unit (I) derived from a hydroxycarboxylic acid: [ka] (In the above formula (I), Ar 1 is selected from the group consisting of an optionally substituted phenyl group, a biphenyl group, a 4,4'-isopropylidenediphenyl group, a naphthyl group, an anthryl group and a phenanthryl group. It is preferred that the compound contains
[0015] In an embodiment of the present invention, the liquid crystal polymer resin comprises the following structural unit (II) derived from a diol compound: [ka] (In the above formula (II), Ar 2 is selected from the group consisting of an optionally substituted phenyl group, a biphenyl group, a 4,4'-isopropylidenediphenyl group, a naphthyl group, an anthryl group and a phenanthryl group, and The following structural unit (III) derived from a dicarboxylic acid: [ka] (In the above formula (III), Ar 3 is selected from the group consisting of an optionally substituted phenyl group, a biphenyl group, a 4,4'-isopropylidenediphenyl group, a naphthyl group, an anthryl group and a phenanthryl group. It is preferred that the composition further comprises:
[0016] In an embodiment of the present invention, the liquid crystal polymer resin comprises the following structural unit (IV): [ka] It is preferred that the composition further comprises:
[0017] In an embodiment of the present invention, the liquid crystal polymer resin comprises the following structural unit (V): [ka] It is preferred that the composition further comprises:
[0018] In an aspect of the present invention, the inorganic filler is preferably at least one selected from the group consisting of talc, mica, glass, silica, wollastonite, barium sulfate, calcium pyrophosphate, calcium sulfate, calcium titanate, calcium carbonate, zinc oxide, titanium oxide, carbon black, and carbon fiber.
[0019] In this aspect of the present invention, the adhesive is preferably an epoxy adhesive and / or an acrylate adhesive.
[0020] In another aspect of the present invention, there is provided a resin composition for use in a method for improving adhesive strength of a resin molded product to an adhesive, comprising: A resin composition is provided that includes 50 parts by mass or more and 99 parts by mass or less of a liquid crystal polymer resin, 1 part by mass or more and 50 parts by mass or less of an amorphous resin, and 0.1 parts by mass or more and 120 parts by mass or less of an inorganic filler per 100 parts by mass of the total of the liquid crystal polymer resin and the amorphous resin.
[0021] According to another aspect of the present invention, there is provided a composite obtained by bonding a resin molded product made of a resin composition containing 50 parts by mass or more and 99 parts by mass or less of a liquid crystal polymer resin, 1 part by mass or more and 50 parts by mass or less of an amorphous resin, and 0.1 parts by mass or more and 120 parts by mass or less of an inorganic filler per 100 parts by mass of the total of the liquid crystal polymer resin and the amorphous resin, with an adhesive, to another member.
[0022] In another aspect of the present invention, the adhesive is preferably an epoxy adhesive and / or an acrylate adhesive.
[0023] According to yet another aspect of the present invention, there is provided a camera module part including the above-mentioned composite as a constituent member. Effect of the Invention
[0024] According to the present invention, it is possible to provide a method for improving the adhesive strength of a resin molded product against an adhesive without impairing the mechanical strength of the resin molded product. Also, according to the present invention, it is possible to provide a composite body having improved adhesive strength, which is formed by bonding a resin molded product to another member with an adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] [Method for improving adhesive strength of resin molded products to adhesives] In the present invention, by blending at least a liquid crystal polymer resin, an amorphous resin and an inorganic filler in specific ratios into the resin composition that forms the resin molded product, it is possible to improve the adhesive strength to an adhesive without impairing the mechanical strength of the obtained resin molded product.
[0026] Usually, resin molded products containing only liquid crystal polymer resin as a resin component often cannot exhibit sufficient adhesion to conventionally known adhesives (for example, epoxy adhesives and acrylate adhesives). The reason for this is that in resin molded products containing only liquid crystal polymer resin as a resin component, a layer called a skin layer that is easily peeled off is formed on the surface of the resin molded product, which is presumed to be one of the reasons for the low adhesive strength of the liquid crystal polymer resin. On the other hand, in the present invention, by blending an amorphous resin in addition to the liquid crystal polymer resin as a resin component, it is possible to improve the adhesive strength to adhesives such as epoxy adhesives and acrylate adhesives. The reason for this is presumed to be that the amorphous resin exposed on the surface of the resin molded product can increase the adhesiveness with the adhesive. In addition, it is presumed that blending an amorphous resin as a resin component relaxes the orientation of the liquid crystal polymer resin, thereby slightly relaxing the formation of the skin layer, and the interface between the skin layer and the inner core layer becomes unclear, making it difficult for the skin layer to peel off, thereby increasing the adhesiveness. Below, each component contained in the resin composition will be explained.
[0027] (Liquid crystal polymer resin) The liquid crystal polymer resin to be blended in the resin composition preferably contains at least the structural unit (I) derived from hydroxycarboxylic acid, and may further contain the structural unit (II) derived from diol compound and the structural unit (III) derived from dicarboxylic acid. The resin composition may contain only one type of liquid crystal polymer resin, or may contain two or more types. Hereinafter, each structural unit contained in the liquid crystal polymer resin will be described.
[0028] (Structural unit (I) derived from hydroxycarboxylic acid) The unit (I) constituting the liquid crystal polymer resin is a constituent unit derived from an aromatic hydroxycarboxylic acid represented by the following formula (I): The constituent unit (I) may be contained in one type or in two or more types.
[0029] [ka] In the above formula, Ar1 is selected from the group consisting of a phenyl group, a biphenyl group, a 4,4'-isopropylidenediphenyl group, a naphthyl group, an anthryl group and a phenanthryl group, which may have a substituent. Among these, a phenyl group, a biphenyl group and a naphthyl group are preferred, and a naphthyl group is more preferred. Examples of the substituent include hydrogen, an alkyl group, an alkoxy group, and fluorine. The number of carbon atoms in the alkyl group is preferably 1 to 10, and more preferably 1 to 5. The alkyl group may be either a linear alkyl group or a branched alkyl group. The number of carbon atoms in the alkoxy group is preferably 1 to 10, and more preferably 1 to 5.
[0030] Examples of monomers that provide the structural unit represented by formula (I) above include 6-hydroxy-2-naphthoic acid (HNA, formula (1) below), p-hydroxybenzoic acid (HBA, formula (2) below), and acylation products, ester derivatives, and acid halides thereof. [ka] [ka]
[0031] The composition ratio (mol%) of the structural unit (I) to the structural units of the entire liquid crystal polymer resin is preferably 30 mol% or more, more preferably 35 mol% or more, even more preferably 40 mol% or more, and even more preferably 45 mol% or more as the lower limit, and preferably 100 mol% or less, more preferably 95 mol% or less, even more preferably 90 mol% or less, and even more preferably 85 mol% or less as the upper limit.When two or more structural units (I) are included, the total molar ratio thereof may be within the above composition ratio range.
[0032] (Structural unit (II) derived from a diol compound) The unit (II) constituting the liquid crystal polymer resin is a constituent unit derived from an aromatic diol compound represented by the following formula (II): The constituent unit (II) may be contained in one type or in two or more types.
[0033] [ka] In the above formula, Ar 2 is selected from the group consisting of a phenyl group, a biphenyl group, a 4,4'-isopropylidenediphenyl group, a naphthyl group, an anthryl group and a phenanthryl group, which may have a substituent. Among these, a phenyl group and a biphenyl group are more preferable. Examples of the substituent include hydrogen, an alkyl group, an alkoxy group, and fluorine. The number of carbon atoms in the alkyl group is preferably 1 to 10, and more preferably 1 to 5. The alkyl group may be either a linear alkyl group or a branched alkyl group. The number of carbon atoms in the alkoxy group is preferably 1 to 10, and more preferably 1 to 5.
[0034] Examples of monomers that provide the structural unit (II) include 4,4'-dihydroxybiphenyl (BP, formula (3) below), hydroquinone (HQ, formula (4) below), methylhydroquinone (MeHQ, formula (5) below), 4,4'-isopropylidenediphenol (BisPA, formula (6) below), resorcinol, and acylated products thereof, ester derivatives, acid halides, etc. Among these, it is preferable to use 4,4'-dihydroxybiphenyl (BP) and acylated products thereof, ester derivatives, and acid halides. [ka] [ka] [ka] [ka]
[0035] The composition ratio (mol%) of the structural unit (II) to the structural unit of the entire liquid crystal polymer resin is preferably 0 mol% or more, more preferably 2.5 mol% or more, even more preferably 5 mol% or more, and even more preferably 7.5 mol% or more, and the upper limit is preferably 35 mol% or less, more preferably 32.5 mol% or less, even more preferably 30 mol% or less, and even more preferably 27.5 mol% or less. When two or more structural units (II) are included, the total molar ratio thereof may be within the above composition ratio range.
[0036] (Structural unit (III) derived from aromatic dicarboxylic acid) The unit (III) constituting the liquid crystal polymer resin is a constituent unit derived from an aromatic dicarboxylic acid represented by the following formula (III): The constituent unit (III) may be contained in one type or in two or more types.
[0037] [ka] In the above formula, Ar 3 is selected from the group consisting of a phenyl group, a biphenyl group, a 4,4'-isopropylidenediphenyl group, a naphthyl group, an anthryl group and a phenanthryl group, which may have a substituent. Among these, a phenyl group and a biphenyl group are more preferable. Examples of the substituent include hydrogen, an alkyl group, an alkoxy group and fluorine. The number of carbon atoms in the alkyl group is preferably 1 to 10, more preferably 1 to 5. The alkyl group may be either a linear alkyl group or a branched alkyl group. The number of carbon atoms in the alkoxy group is preferably 1 to 10, more preferably 1 to 5.
[0038] Examples of monomers that provide the structural unit (III) include terephthalic acid (TPA, formula (7) below), isophthalic acid (IPA, formula (8) below), 2,6-naphthalenedicarboxylic acid (NADA, formula (9) below), and their acylation products, ester derivatives, and acid halides. [ka] [ka] [ka]
[0039] The composition ratio (mol%) of the structural unit (III) relative to the entire structural unit of the liquid crystal polymer resin is preferably 0 mol% or more, more preferably 2.5 mol% or more, even more preferably 5 mol% or more, and even more preferably 7.5 mol% or more, and the upper limit is preferably 35 mol% or less, more preferably 32.5 mol% or less, even more preferably 30 mol% or less, and even more preferably 27.5 mol% or less. When two or more types of structural unit (II) are included, the total molar ratio thereof may be within the above composition ratio range. The composition ratio of the structural unit (II) and the composition ratio of the structural unit (III) are substantially equivalent ((structural unit (II) ≒ structural unit (III)).
[0040] (Structural unit (IV)) The liquid crystal polymer resin may further contain the following structural unit (IV) in addition to the above structural units (I) to (III). [ka] Examples include:
[0041] Examples of monomers that provide the structural unit (IV) include acetaminophenone (AAP, formula (10) below), p-aminophenol, 4'-acetoxyacetanilide, and acylation products, ester derivatives, and acid halides thereof. [ka]
[0042] (Structural unit (V)) The liquid crystal polymer resin may further contain the following structural unit (V) in addition to the above structural units (I) to (III). [ka] Examples include:
[0043] Examples of monomers that provide the structural unit (V) include 1,4-cyclohexanedicarboxylic acid (CHDA, formula (11) below) and acylation products, ester derivatives, and acid halides thereof. [ka]
[0044] The composition ratio (mol%) of the structural units (IV) and (V) to the entire structural units of the liquid crystal polymer resin can be appropriately set according to the composition ratio of the structural units (I) to (III). For example, after setting the composition ratio of the structural unit (I), the composition ratio of the structural units (II), (III), (IV) and (V) may be appropriately set so that the monomer ratio (molar ratio) of the carboxyl group to the hydroxyl group and / or amine group in the monomer charge is in the range of approximately 1:1. The total composition ratio of the structural units (II) and (IV) and the total composition ratio of the structural units (III) and (V) are substantially equivalent ((structural unit (II) + (IV) ≒ structural unit (III) + (V)).
[0045] The liquid crystallinity of the liquid crystal polymer resin can be confirmed by using a polarizing microscope (product name: BH-2) manufactured by Olympus Corporation equipped with a hot stage for a microscope (product name: FP82HT) manufactured by Mettler, and then heating and melting the liquid crystal polymer resin on the heating stage of the microscope, and observing whether or not it has optical anisotropy.
[0046] (Method of manufacturing liquid crystal polymer resin) The liquid crystal polymer resin can be produced by polymerizing the monomers that provide the structural units (I) to (III) and, if desired, the monomers that provide the structural units (IV) and (V) by a conventionally known method. In one embodiment, the liquid crystal polymer resin can also be produced by a two-stage polymerization in which a prepolymer is prepared by melt polymerization and then this is further polymerized in a solid phase.
[0047] From the viewpoint of efficiently obtaining a liquid crystal polymer resin, the melt polymerization is preferably carried out under reflux of acetic acid in the presence of 1.03 to 1.15 molar equivalents of acetic anhydride relative to the total hydroxyl groups of the monomers, with the monomers that optionally give the above-mentioned structural units (I) to (III) and, optionally, (IV) and (V) combined in a predetermined ratio to make up 100 mol %.
[0048] When the polymerization reaction is carried out in two stages, melt polymerization followed by solid-state polymerization, the prepolymer obtained by melt polymerization is cooled and solidified, pulverized into powder or flakes, and then a known solid-state polymerization method, for example, a method of heat-treating the prepolymer resin in an inert atmosphere such as nitrogen or in vacuum at a temperature range of 200 to 350° C. for 1 to 30 hours, is preferably selected. The solid-state polymerization may be carried out with stirring, or may be carried out in a stationary state without stirring.
[0049] A catalyst may or may not be used in the polymerization reaction. As the catalyst to be used, a catalyst conventionally known as a catalyst for polymerization of liquid crystal polymers can be used, and examples of the catalyst include metal salt catalysts such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, and antimony trioxide, nitrogen-containing heterocyclic compounds such as N-methylimidazole, and organic compound catalysts. The amount of the catalyst to be used is not particularly limited, but is preferably 0.0001 to 0.1 parts by weight relative to 100 parts by weight of the total amount of monomers.
[0050] The polymerization reactor for melt polymerization is not particularly limited, but a reactor generally used for reactions of high-viscosity fluids is preferably used. Examples of such reactors include stirring tank-type polymerization reactors having stirring devices with stirring blades of various shapes, such as anchor type, multi-stage type, spiral belt type, spiral shaft type, etc., or modified versions of these, and mixing devices generally used for kneading resins, such as kneaders, roll mills, and Banbury mixers.
[0051] (amorphous resin) Examples of the amorphous resin to be blended in the resin composition include polyarylate, polyethersulfone, polysulfone, polyphenylsulfone, polyphenylether, and polycarbonate, and polyarylate and polysulfone are preferred, and polyarylate is more preferred. Only one type of amorphous resin may be used, or two or more types may be used.
[0052] The polyarylate is an amorphous aromatic polyester polymer consisting of an aromatic dicarboxylic acid or its derivative and a dihydric phenol or its derivative. Examples of raw materials for introducing aromatic dicarboxylic acid residues include terephthalic acid, isophthalic acid, phthalic acid, chlorophthalic acid, nitrophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, methylterephthalic acid, 4,4'-biphenyldicarboxylic acid, 2,2'-biphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-diphenylmethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 4,4'-diphenylisopropylidenedicarboxylic acid, 1,2-bis(4-carboxyphenoxy)ethane, and 5-sodium sulfoisophthalic acid. The raw material for introducing the bisphenol residue is bisphenol, and specific examples thereof include resorcinol, 4,4'-isopropylidenediphenol, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl ketone, 4,4'-dihydroxydiphenylmethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 3,3,5-trimethyl-1,1-bis(4-hydroxyphenyl)cyclohexane.
[0053] (Inorganic filler) Examples of inorganic fillers to be mixed into the resin composition include talc, mica, glass, silica, wollastonite, barium sulfate, calcium pyrophosphate, calcium sulfate, calcium titanate, calcium carbonate, zinc oxide, titanium oxide, carbon black, and carbon fiber. Among these, talc and wollastonite are preferably used. The shape of the inorganic filler is not particularly limited and can be appropriately selected. Only one type of inorganic filler may be used, or two or more types may be used.
[0054] Typically, the amount of the resin components in the resin composition (the total amount of the liquid crystal polymer resin and the amorphous resin) relative to the entire resin composition is, as a lower limit, preferably 30 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 45 parts by mass or more, and even more preferably 50 parts by mass or more, and as an upper limit, preferably 90 parts by mass or less, more preferably 85 parts by mass or less, even more preferably 80 parts by mass or less, and even more preferably 75 parts by mass or less.
[0055] In the resin composition, the amount of the liquid crystal polymer resin is adjusted to 50 parts by mass or more and 99 parts by mass or less, the amount of the amorphous resin is adjusted to 1 part by mass or more and 50 parts by mass or less, and the amount of the inorganic filler is adjusted to 0.1 parts by mass or more and 120 parts by mass or less, relative to 100 parts by mass of the total of the liquid crystal polymer resin and the amorphous resin, so that the adhesive strength of the resin molded product made of the resin composition to the adhesive can be improved. The amount of the liquid crystal polymer resin is preferably 60 parts by mass or more, more preferably 62 parts by mass or more, and even more preferably 65 parts by mass or more, relative to 100 parts by mass of the total of the liquid crystal polymer resin and the amorphous resin. The amount of the amorphous resin is preferably 40 parts by mass or less, more preferably 38 parts by mass or less, and even more preferably 35 parts by mass or less, relative to 100 parts by mass of the total of the liquid crystal polymer resin and the amorphous resin. The amount of the inorganic filler to be blended is preferably 1 part by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, and is preferably 110 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 90 parts by mass or less, as the lower limit. By adjusting the blending amount of each component, it is possible to further improve the adhesive strength to the adhesive without impairing the mechanical strength of the resin molded product.
[0056] (Epoxy group-containing copolymer) The resin composition may further contain an epoxy group-containing copolymer. By containing an epoxy group-containing copolymer in the resin composition, the adhesive strength to an adhesive can be further improved.
[0057] The epoxy group-containing copolymer is not particularly limited, and examples thereof include epoxy group-containing olefin-based copolymers and epoxy group-containing styrene-based copolymers. The epoxy group-containing olefin-based copolymer is, for example, a copolymer composed of a structural unit derived from an α-olefin and a structural unit derived from a glycidyl ester of an α,β-unsaturated acid. The α-olefin is not particularly limited, and examples thereof include ethylene, propylene, butene, and among these, ethylene is preferred. The epoxy group-containing styrene-based copolymer is, for example, a copolymer composed of a structural unit derived from a styrene and a structural unit derived from a glycidyl ester of an α,β-unsaturated acid. The styrene is, for example, styrene, α-methylstyrene, brominated styrene, divinylbenzene, and among these, styrene is preferred.
[0058] The amount of the epoxy group-containing copolymer blended is preferably 1 part by mass or more and 5 parts by mass or less, more preferably 2 parts by mass or more and 4 parts by mass or less, based on 100 parts by mass in total of the liquid crystal polymer resin and the amorphous resin.
[0059] (Other additives) The resin composition may contain other additives as long as they do not impair the effects of the present invention, such as colorants, dispersants, plasticizers, antioxidants, curing agents, flame retardants, heat stabilizers, UV absorbers, antistatic agents, surfactants, release agents, and lubricants.
[0060] The amount of other additives added in the resin composition is preferably 5 parts by mass or less, and more preferably 2 parts by mass or less, per 100 parts by mass of the liquid crystal polymer resin and the amorphous resin in total.
[0061] (Complex) The composite according to the present invention is formed by bonding a resin molded article made of the above-mentioned resin composition to another member with an adhesive. Such a composite has excellent adhesive strength between the resin molded article and the other member, and can be used in various applications requiring adhesive strength.
[0062] (Method of Manufacturing the Composite) In the present invention, a resin composition containing the above-mentioned liquid crystal polymer resin, amorphous resin, inorganic filler, and other additives, etc., in a specific ratio can be molded by a conventionally known method to obtain the resin composition. The resin composition can be obtained by melt-kneading the above-mentioned liquid crystal polymer resin, amorphous resin, inorganic filler, and other additives, etc., using a Banbury mixer, kneader, single-screw or twin-screw extruder, etc.
[0063] Examples of the molding method include press molding, blow molding, foam molding, injection molding, extrusion molding, and punch molding. Among them, melt molding such as injection molding and extrusion molding is preferred, and injection molding is more preferred. The resin molded product produced as described above can be processed into various shapes depending on the application. The shape of the molded product can be, for example, a plate shape, a film shape, etc.
[0064] Then, the obtained resin molded article is bonded to another member using an adhesive to produce a composite body. The adhesive is not particularly limited, but examples thereof include an epoxy adhesive and an acrylate adhesive.
[0065] (Camera module parts) The camera module part according to the present invention includes the above-mentioned composite as a constituent member. The camera module part can be used for various applications such as actuator components, lens barrel parts, mount holder parts, CMOS (image sensor) frames, shutters and shutter bobbins in mobile phones, laptop computers, digital cameras, digital video cameras, car-mounted cameras, surveillance cameras, drones, smart watches, smartphones, cameras mounted on tablet terminals, etc. In such applications, the application area of the adhesive is small due to miniaturization, but the camera module part has excellent adhesive strength between the resin molded product and other members, and therefore has excellent impact resistance. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0067] <Production of Liquid Crystal Polymer Resin> (Synthesis Example 1) Into a polymerization vessel equipped with an agitator, 60 mol% p-hydroxybenzoic acid (HBA), 20 mol% 4,4'-dihydroxybiphenyl (BP), 15 mol% terephthalic acid (TPA), and 5 mol% isophthalic acid (IPA) were added as raw monomers, and potassium acetate and magnesium acetate were charged as catalysts. The polymerization vessel was depressurized and nitrogen was injected twice to replace the atmosphere with nitrogen. Then, acetic anhydride (1.05 molar equivalents relative to the hydroxyl groups) was further added, and the temperature was raised to 150°C. The acetylation reaction was carried out under reflux for 2 hours.
[0068] After the acetylation was completed, the polymerization vessel in which acetic acid was distilled was heated at a rate of 0.5°C / min, and when the melt temperature in the vessel reached 305°C, the polymer was taken out and cooled to solidify. The obtained polymer was pulverized to a size that could pass through a sieve with 2.0 mm openings to obtain a prepolymer.
[0069] Next, the prepolymer obtained above was heated from room temperature to 295°C over 11 hours in an oven to carry out solid-phase polymerization. It was then allowed to naturally cool at room temperature to obtain liquid crystal polymer resin 1. Using a polarizing microscope (product name: BH-2) manufactured by Olympus Corporation equipped with a hot stage for microscopes (product name: FP82HT) manufactured by Mettler, liquid crystal polymer resin 1 was heated and melted on the microscope heating stage, and it was confirmed that it exhibited liquid crystallinity based on the presence or absence of optical anisotropy.
[0070] (Synthesis Example 2) A polymerization vessel equipped with a stirring blade was charged with the raw monomers HBA (60 mol%), BP (15 mol%), TPA (7 mol%), IPA (3 mol%), acetaminophenone (AAP) (5 mol%), and 1,4-cyclohexanedicarboxylic acid (CHDA) (10 mol%). Potassium acetate and magnesium acetate were also charged as catalysts. The polymerization vessel was depressurized and nitrogen was injected twice to replace the nitrogen. Then, acetic anhydride (1.05 molar equivalents relative to the hydroxyl groups) was further added, and the temperature was raised to 150°C. The acetylation reaction was carried out under reflux for 2 hours.
[0071] After the acetylation was completed, the polymerization vessel in which acetic acid was distilled was heated at a rate of 0.5°C / min, and when the melt temperature in the vessel reached 300°C, the polymer was taken out and cooled to solidify. The obtained polymer was pulverized to a size that could pass through a sieve with 2.0 mm openings to obtain a prepolymer.
[0072] Next, the prepolymer obtained above was heated in an oven from room temperature to 300°C over 8 hours, and then the temperature was maintained at 300°C for 1 hour to carry out solid-phase polymerization. Then, the prepolymer was naturally cooled at room temperature to obtain liquid crystal polymer resin 2. Using a polarizing microscope (product name: BH-2) manufactured by Olympus Corporation equipped with a hot stage for microscopes (product name: FP82HT) manufactured by Mettler, liquid crystal polymer resin 2 was heated and melted on the microscope heating stage, and it was confirmed that the resin exhibited liquid crystallinity based on the presence or absence of optical anisotropy.
[0073] (Synthesis Example 3) Into a polymerization vessel equipped with an agitator with a torque meter, 73 mol% of HBA and 27 mol% of 6-hydroxy-2-naphthoic acid (HNA) were added as raw material monomers, and potassium acetate and magnesium acetate were charged as catalysts. The polymerization vessel was depressurized and nitrogen was injected twice to replace the atmosphere with nitrogen. Then, acetic anhydride (1.03 molar equivalents relative to the hydroxyl group) was further added, and the temperature was raised to 150°C. An acetylation reaction was carried out under reflux for 30 minutes.
[0074] After the acetylation was completed, the polymerization vessel in the acetic acid distillation state was heated at 0.5°C / min, and when the melt temperature in the vessel reached 320°C, the pressure was reduced to 10 mmHg over 80 minutes. After the stirring torque reached a predetermined value, nitrogen was introduced to change the state from reduced pressure to normal pressure and then to pressurized state, and the liquid crystal polymer resin 3 was discharged from the bottom of the polymerization vessel. The liquid crystal polymer resin 3 was heated and melted on the microscope heating stage using a polarizing microscope (product name: BH-2) manufactured by Olympus Corporation equipped with a microscope hot stage (product name: FP82HT) manufactured by Mettler, and it was confirmed that the liquid crystal polymer resin 3 exhibited liquid crystallinity based on the presence or absence of optical anisotropy.
[0075] (Synthesis Example 4) Into a polymerization vessel equipped with a stirring blade, 62 mol% HBA, 10 mol% HNA, 6 mol% BP, 8 mol% hydroquinone (HQ), and 14 mol% TPA were added as raw material monomers, and potassium acetate and magnesium acetate were charged as catalysts. The polymerization vessel was depressurized and nitrogen was injected three times to replace the nitrogen, after which acetic anhydride (1.08 molar equivalents relative to the hydroxyl groups) was further added, the temperature was raised to 150°C, and the acetylation reaction was carried out under reflux for 2 hours.
[0076] After the acetylation was completed, the polymerization vessel in which acetic acid was distilled was heated at a rate of 0.5°C / min, and when the melt temperature in the vessel reached 310°C, the polymer was taken out and cooled to solidify. The obtained polymer was pulverized to a size that could pass through a sieve with 1.0 mm openings to obtain a prepolymer.
[0077] Next, the prepolymer obtained above was heated in an oven from room temperature to 290°C over 12 hours, and then the temperature was maintained at 290°C for 1 hour to carry out solid-phase polymerization. Then, the prepolymer was naturally cooled at room temperature to obtain liquid crystal polymer resin 4. Using a polarizing microscope (product name: BH-2) manufactured by Olympus Corporation equipped with a hot stage for microscopes (product name: FP82HT) manufactured by Mettler, liquid crystal polymer resin 4 was heated and melted on the microscope heating stage, and it was confirmed that the resin exhibited liquid crystallinity based on the presence or absence of optical anisotropy.
[0078] (Synthesis Example 5) Into a polymerization vessel equipped with a stirring blade, 60 mol% HBA, 20 mol% BP, 15 mol% TPA, and 5 mol% IPA were added as raw material monomers, and potassium acetate and magnesium acetate were charged as catalysts. The polymerization vessel was depressurized and nitrogen was injected twice to replace the atmosphere with nitrogen. Then, acetic anhydride (1.05 molar equivalents relative to the hydroxyl groups) was further added, and the temperature was raised to 150°C. An acetylation reaction was carried out under reflux for 2 hours.
[0079] After the acetylation was completed, the polymerization vessel in which acetic acid was distilled was heated at a rate of 0.5°C / min, and when the melt temperature in the vessel reached 305°C, the polymer was taken out and cooled to solidify. The obtained polymer was pulverized to a size that could pass through a sieve with 2.0 mm openings to obtain a prepolymer.
[0080] Next, the prepolymer obtained above was heated from room temperature to 250°C over 8.5 hours in an oven to carry out solid-phase polymerization. It was then allowed to naturally cool at room temperature to obtain liquid crystal polymer resin 5. Using a polarizing microscope (product name: BH-2) manufactured by Olympus Corporation equipped with a hot stage for microscopes (product name: FP82HT) manufactured by Mettler, liquid crystal polymer resin 5 was heated and melted on the microscope heating stage, and it was confirmed that it exhibited liquid crystallinity based on the presence or absence of optical anisotropy.
[0081] The structural units (monomer compositions) of the liquid crystal polymers 1 to 5 obtained above are shown in Table 1. [Table 1]
[0082] <Preparation of amorphous resin> The following amorphous resins were prepared. Polyarylate 1 (PAR1) (Unitika Ltd., product name: U Polymer U-100 L type) Polyarylate 2 (PAR2) (Unitika Ltd., product name: U Polymer U-100 C type) Polyarylate 3 (PAR3) (manufactured by Unitika Ltd., product name: U Polymer U-100 D type) Polyethersulfone 1 (PESU1) (Solvay, product name: Virantage VW-10200 RFP) Polyethersulfone 2 (PESU2) (Solvay, product name: Virantage VW-10700 RFP) Polysulfone (PSU) (manufactured by Solvay, product name: Udel P-1700 NT 11) Polyphenyl ether (PPE) (Mitsubishi Engineering Plastics Corporation, product name: IUPIACE PX100L) Polycarbonate (PC) (manufactured by Sumika Polycarbonate Co., Ltd., product name: SD2201W)
[0083] <Preparation of inorganic filler> The following inorganic fillers were prepared: Talc 1 (manufactured by Nippon Talc Co., Ltd., product name: MS-KY) Talc 2 (manufactured by Hayashi Kasei Co., Ltd., product name: PK-C) Wollastonite (Kansai Matec Co., Ltd., product name: KGP-H45) Barium sulfate (manufactured by Sakai Chemical Industry Co., Ltd., product name: BARIACE B-55) Calcium pyrophosphate (manufactured by Taihei Chemical Industry Co., Ltd., product name: calcium pyrophosphate) Titanium oxide (manufactured by Sakai Chemical Industry Co., Ltd., product name: D2378) Mica (manufactured by Yamaguchi Mica Co., Ltd., product name: AB-25S) Glass fiber (manufactured by Central Glass Fiber Co., Ltd., product name: EFH150-01)
[0084] <Preparation of epoxy group-containing copolymer> The following epoxy group-containing copolymer was prepared. Epoxy group-containing copolymer (manufactured by Sumitomo Chemical Co., Ltd., product name: Bondfast 2C)
[0085] <Production of Resin Composition> Example 1 70.0 parts by mass of the liquid crystal polymer resin 1 obtained above and 28.6 parts by mass of the liquid crystal polymer resin 2 (total of 98.6 parts by mass of the liquid crystal polymer resins) were dry blended with 1.4 parts by mass of the above PAR1 and 42.9 parts by mass of the above talc 1, and then kneaded at a temperature of 380°C in a twin-screw extruder (PCM30, manufactured by Ikegai Corporation), strand-cut and pelletized to obtain a pellet-shaped resin composition.
[0086] Example 2 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 67.1 parts by mass of the liquid crystal polymer resin 1 obtained above, 28.6 parts by mass of the liquid crystal polymer resin 2 (total liquid crystal polymer resin: 95.7 parts by mass), 4.3 parts by mass of the above PAR1, and 42.9 parts by mass of the above talc 1 were dry-blended.
[0087] Comparative Example 1 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 71.4 parts by mass of the liquid crystal polymer resin 1 obtained above, 28.6 parts by mass of the liquid crystal polymer resin 2 (total of 100 parts by mass of the liquid crystal polymer resins) were dry-blended with 42.9 parts by mass of the above talc.
[0088] Example 3 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 93.8 parts by mass of the liquid crystal polymer resin 1 obtained above, 6.3 parts by mass of the above PAR1, and 25.0 parts by mass of the above wollastonite were dry blended.
[0089] Example 4 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 62.5 parts by mass of the liquid crystal polymer resin 1 obtained above, 37.5 parts by mass of the above PESU1, and 25.0 parts by mass of the above wollastonite were dry blended.
[0090] Example 5 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 87.5 parts by mass of the liquid crystal polymer resin 1 obtained above, 12.5 parts by mass of the above PSU, and 25.0 parts by mass of the above wollastonite were dry blended.
[0091] Comparative Example 2 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 100 parts by mass of the liquid crystal polymer resin 1 obtained above and 25.0 parts by mass of the wollastonite were dry-blended.
[0092] Example 6 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 90.9 parts by mass of the liquid crystal polymer resin 1 obtained above, 9.1 parts by mass of the above PAR1, and 81.8 parts by mass of the above talc 1 were dry blended.
[0093] Example 7 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 90.9 parts by mass of the liquid crystal polymer resin 1 obtained above, 9.1 parts by mass of the above PAR2, and 81.8 parts by mass of the above talc 1 were dry blended.
[0094] Example 8 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 90.9 parts by mass of the liquid crystal polymer resin 1 obtained above, 9.1 parts by mass of the above PAR3, and 81.8 parts by mass of the above talc 1 were dry blended.
[0095] Comparative Example 3 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 100 parts by mass of the liquid crystal polymer resin 1 obtained above and 81.8 parts by mass of the talc 1 above were dry-blended.
[0096] Example 9 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 85.7 parts by mass of the liquid crystal polymer resin 2 obtained above, 14.3 parts by mass of the above PAR1, and 42.9 parts by mass of the above talc 1 were dry blended and kneaded at a temperature of 360°C.
[0097] Example 10 A pellet-shaped resin composition was obtained in the same manner as in Example 9, except that 85.7 parts by mass of the liquid crystal polymer resin 2 obtained above, 14.3 parts by mass of the above PESU2, and 42.9 parts by mass of the above talc 1 were dry blended.
[0098] Example 11 A pellet-shaped resin composition was obtained in the same manner as in Example 9, except that 85.7 parts by mass of the liquid crystal polymer resin 2 obtained above, 14.3 parts by mass of the above PSU, and 42.9 parts by mass of the above talc 1 were dry blended.
[0099] Comparative Example 4 A pellet-shaped resin composition was obtained in the same manner as in Example 9, except that 100 parts by mass of the liquid crystal polymer resin 2 obtained above and 42.9 parts by mass of the talc 1 above were dry-blended.
[0100] Example 12 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 92.9 parts by mass of the liquid crystal polymer resin 1 obtained above, 7.1 parts by mass of the above PAR1, and 42.9 parts by mass of the above talc 1 were dry blended.
[0101] Example 13 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 85.7 parts by mass of the liquid crystal polymer resin 1 obtained above, 14.3 parts by mass of the above PAR1, and 42.9 parts by mass of the above talc 1 were dry blended.
[0102] Example 14 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 71.4 parts by mass of the liquid crystal polymer resin 1 obtained above, 28.6 parts by mass of the above PAR1, and 42.9 parts by mass of the above talc 1 were dry blended.
[0103] Example 15 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 85.7 parts by mass of the liquid crystal polymer resin 1 obtained above, 14.3 parts by mass of the above PAR2, and 42.9 parts by mass of the above talc 1 were dry blended.
[0104] (Example 16) A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 85.7 parts by mass of the liquid crystal polymer resin 1 obtained above, 14.3 parts by mass of the above PSU, and 42.9 parts by mass of the above talc 1 were dry blended.
[0105] (Example 17) A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 92.9 parts by mass of the liquid crystal polymer resin 1 obtained above, 7.1 parts by mass of the above PPE, and 42.9 parts by mass of the above talc 1 were dry blended.
[0106] (Example 18) A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 85.7 parts by mass of the liquid crystal polymer resin 1 obtained above, 14.3 parts by mass of the above PPE, and 42.9 parts by mass of the above talc 1 were dry blended.
[0107] Comparative Example 5 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 100 parts by mass of the liquid crystal polymer resin 1 obtained above and 42.9 parts by mass of the talc 1 above were dry-blended.
[0108] (Example 19) A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 78.5 parts by mass of the liquid crystal polymer resin 1 obtained above, 13.8 parts by mass of the liquid crystal polymer resin 5 (total liquid crystal polymer resin: 92.3 parts by mass), 7.7 parts by mass of the above PPE, and 53.8 parts by mass of the above talc 1 were dry-blended.
[0109] Comparative Example 6 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 86.2 parts by mass of the liquid crystal polymer resin 1 obtained above, 13.8 parts by mass of the liquid crystal polymer resin 5 (total of 100 parts by mass of the liquid crystal polymer resins) were dry-blended with 53.8 parts by mass of the talc 1 obtained above.
[0110] (Example 20) A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 90.0 parts by mass of the liquid crystal polymer resin 3 obtained above, 10.0 parts by mass of the PAR1 described above, 40.0 parts by mass of the talc 2 described above, 50.0 parts by mass of the calcium pyrophosphate described above, and 10.0 parts by mass of the barium sulfate described above were dry-blended and kneaded at a temperature of 330°C.
[0111] Example 21 A pellet-shaped resin composition was obtained in the same manner as in Example 20, except that 90.0 parts by mass of the liquid crystal polymer resin 3 obtained above, 10.0 parts by mass of the above PC, 40.0 parts by mass of the above talc 2, 50.0 parts by mass of the above calcium pyrophosphate, and 10.0 parts by mass of the above barium sulfate were dry blended.
[0112] Comparative Example 7 A pellet-shaped resin composition was obtained in the same manner as in Example 20, except that 100.0 parts by mass of the liquid crystal polymer resin 3 obtained above, 40.0 parts by mass of the talc 2 above, 50.0 parts by mass of the calcium pyrophosphate above, and 10.0 parts by mass of the barium sulfate above were dry-blended.
[0113] Example 22 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 90.0 parts by mass of the liquid crystal polymer resin 4 obtained above, 10.0 parts by mass of the PAR1 described above, 40.0 parts by mass of the talc 2 described above, 50.0 parts by mass of the calcium pyrophosphate described above, and 10.0 parts by mass of the titanium oxide described above were dry-blended and kneaded at a temperature of 360°C.
[0114] (Example 23) A pellet-shaped resin composition was obtained in the same manner as in Example 22, except that 75.0 parts by mass of the liquid crystal polymer resin 4 obtained above, 25.0 parts by mass of the PAR1 described above, 40.0 parts by mass of the talc 2 described above, 50.0 parts by mass of the calcium pyrophosphate described above, and 10.0 parts by mass of the titanium oxide described above were dry-blended.
[0115] Example 24 A pellet-shaped resin composition was obtained in the same manner as in Example 22, except that 70.0 parts by mass of the liquid crystal polymer resin 4 obtained above, 30.0 parts by mass of the PAR1 described above, 40.0 parts by mass of the talc 2 described above, 50.0 parts by mass of the calcium pyrophosphate described above, and 10.0 parts by mass of the titanium oxide described above were dry-blended.
[0116] (Example 25) A pellet-shaped resin composition was obtained in the same manner as in Example 22, except that 90.0 parts by mass of the liquid crystal polymer resin 4 obtained above, 10.0 parts by mass of the PAR1 described above, 40.0 parts by mass of the talc 2 described above, 50.0 parts by mass of the calcium pyrophosphate described above, 10.0 parts by mass of the titanium oxide described above, and 2.2 parts by mass of the epoxy group-containing copolymer described above were dry-blended.
[0117] Comparative Example 8 A pellet-shaped resin composition was obtained in the same manner as in Example 22, except that 100.0 parts by mass of the liquid crystal polymer resin 4 obtained above, 40.0 parts by mass of the talc 2 described above, 50.0 parts by mass of the calcium pyrophosphate described above, and 10.0 parts by mass of the titanium oxide described above were dry-blended.
[0118] (Example 26) A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 90.0 parts by mass of the liquid crystal polymer resin 1 obtained above, 10.0 parts by mass of the PAR1 described above, 50.0 parts by mass of the mica described above, and 50.0 parts by mass of the glass fiber described above were dry blended.
[0119] Comparative Example 9 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that 100.0 parts by mass of the liquid crystal polymer resin 1 obtained above, 50.0 parts by mass of the mica described above, and 50.0 parts by mass of the glass fiber described above were dry blended.
[0120] <Production and evaluation of resin molded products> (Measurement of bending strength) The pellet-like resin compositions obtained in the above Examples and Comparative Examples were injection molded using an injection molding machine (SE30DUZ, manufactured by Sumitomo Heavy Industries, Ltd.) at the following maximum cylinder temperature, injection speed of 100 mm / sec, and mold temperature of 80°C to prepare bending test pieces in accordance with ASTM D790. (Maximum cylinder temperature) Examples 1, 2, 9-11, 22-25, Comparative Examples 1, 4, 8: 350° C. Examples 3 to 8, 12 to 19, and 26, and Comparative Examples 2, 3, 5, 6, and 9: 360° C. Examples 20 and 21, Comparative Example 7: 330°C Next, the bending strength (MPa) of the prepared test pieces for bending test was measured in accordance with ASTM D790.
[0121] (Adhesive strength measurement) The pellet-like resin compositions obtained in the above Examples and Comparative Examples were injection molded using an injection molding machine (SE30DU, manufactured by Sumitomo Heavy Industries, Ltd.) at the following maximum cylinder temperature, injection speed of 100 mm / sec, and mold temperature of 80°C to produce molded products of 100 mm x 25 mm x 1.6 mm in accordance with JIS K 6850. (Maximum cylinder temperature) Examples 1, 2, 9-11, 22-25, Comparative Examples 1, 4, 8: 350° C. Examples 3 to 8, 12 to 19, and 26, and Comparative Examples 2, 3, 5, 6, and 9: 360° C. Examples 20 and 21, Comparative Example 7: 330°C Next, the molded product was bonded to the bottom of a stainless steel cylinder with a diameter of 8 mm using an epoxy adhesive (Henkel, 3128NH) to produce a composite. The side of the stainless steel cylinder of the resulting composite was pressed in a direction parallel to the molded product at a position 2.5 mm from the surface of the molded product at a speed of 127 mm / sec, and the adhesive strength (N) at the interface between the molded product and the stainless steel cylinder was measured using a universal testing machine (Instron, 33R 4204 model testing machine).
[0122] Tables 2 and 3 show the components of the resin compositions and the measurement results of the resin molded articles in the above-mentioned Examples 1 to 26 and Comparative Examples 1 to 9.
[0123] [Table 2]
[0124] [Table 3]
[0125] As is clear from the above results, the resin molded products of Examples 1 and 2 had improved adhesive strength to an adhesive without a decrease in bending strength compared to the resin molded product of Comparative Example 1, which had the same type and amount of inorganic filler. The resin molded articles of Examples 3 to 5 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded article of Comparative Example 2 in which the type and amount of inorganic filler was the same. The resin molded articles of Examples 6 to 8 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded article of Comparative Example 3 in which the type and amount of inorganic filler was the same. The resin molded articles of Examples 9 to 11 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded article of Comparative Example 4 in which the type and amount of inorganic filler was the same. The resin molded articles of Examples 12 to 18 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded article of Comparative Example 5 in which the type and amount of inorganic filler was the same. The resin molded product of Example 19 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded product of Comparative Example 6 in which the type and amount of inorganic filler was the same. The resin molded articles of Examples 20 and 21 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded article of Comparative Example 7 in which the type and amount of inorganic filler was the same. The resin molded articles of Examples 22 to 25 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded article of Comparative Example 8 containing the same amount of inorganic filler. The resin molded product of Example 26 had improved adhesive strength to an adhesive with almost no change in bending strength compared to the resin molded product of Comparative Example 9 in which the type and amount of inorganic filler was the same.
Claims
1. A method for improving adhesive strength of a resin molded article to an adhesive when a composite is produced by bonding a resin molded article made of a resin composition containing a liquid crystal polymer resin and an inorganic filler to another member with an epoxy adhesive and / or an acrylate adhesive, comprising the steps of: The resin composition is further blended with an amorphous resin, A method for improving adhesive strength, comprising adjusting the amount of the liquid crystal polymer resin to 50 parts by mass or more and 99 parts by mass or less, the amount of the amorphous resin to 1 part by mass or more and 50 parts by mass or less, and the amount of the inorganic filler to 0.1 parts by mass or more and 120 parts by mass or less, relative to a total of 100 parts by mass of the liquid crystal polymer resin and the amorphous resin.
2. 2. The method for improving adhesive strength according to claim 1, wherein the blending amount of the liquid crystal polymer resin is adjusted to 70 parts by mass or more and 99 parts by mass or less, and the blending amount of the amorphous resin is adjusted to 1 part by mass or more and 30 parts by mass or less.
3. 3. The method for improving adhesive strength according to claim 1, wherein the amorphous resin is at least one selected from the group consisting of polyarylates, polyethersulfones, polysulfones, polyphenyl ethers, and polycarbonates.
4. 3. The method for improving adhesive strength according to claim 1, wherein the amorphous resin is at least one selected from the group consisting of polyarylates and polysulfones.
5. The resin composition further contains 1 part by mass or more and 5 parts by mass or less of an epoxy group-containing copolymer per 100 parts by mass of the liquid crystal polymer resin and the amorphous resin in total. The method for improving adhesive strength according to any one of claims 1 to 4.
6. The method for improving adhesive strength according to any one of claims 1 to 5, wherein the liquid crystal polymer resin contains a structural unit (I) derived from a hydroxycarboxylic acid.
7. The method for improving adhesive strength according to claim 6 , wherein the liquid crystal polymer resin further comprises a structural unit (II) derived from a diol compound and a structural unit (III) derived from a dicarboxylic acid.
8. The liquid crystal polymer resin comprises the following structural unit (IV): 【Chemistry 4】 The method for improving adhesive strength according to claim 6 or 7, further comprising:
9. The liquid crystal polymer resin comprises the following structural unit (V): 【Chemistry 5】 The method for improving adhesive strength according to any one of claims 6 to 8, further comprising:
10. The adhesive strength improving method according to any one of claims 1 to 9, wherein the inorganic filler is at least one selected from the group consisting of talc, mica, glass, silica, wollastonite, barium sulfate, calcium pyrophosphate, calcium sulfate, calcium titanate, calcium carbonate, zinc oxide, titanium oxide, carbon black, and carbon fiber.
11. A resin composition used in a method for improving adhesive strength of a resin molded article to an adhesive when a composite is produced by bonding a resin molded article to another member with an epoxy adhesive and / or an acrylate adhesive, comprising: A resin composition comprising: 50 parts by mass or more and 99 parts by mass or less of a liquid crystal polymer resin; 1 part by mass or more and 50 parts by mass or less of an amorphous resin; and 0.1 parts by mass or more and 120 parts by mass or less of an inorganic filler per 100 parts by mass of the total of the liquid crystal polymer resin and the amorphous resin.
12. A composite obtained by bonding a resin molded product made of a resin composition containing 50 parts by mass or more and 99 parts by mass or less of a liquid crystal polymer resin, 1 part by mass or more and 50 parts by mass or less of an amorphous resin, and 0.1 parts by mass or more and 120 parts by mass or less of an inorganic filler relative to a total of 100 parts by mass of the liquid crystal polymer resin and the amorphous resin, to another member with an epoxy-based adhesive and / or an acrylate-based adhesive.
13. A camera module part comprising the composite of claim 12 as a constituent member.
Citation Information
Patent Citations
Kyakubutanrenhoohoo oyobi sonosochi
JP1976036324A
Refractories tank
JP1980041330A
Method of producing laminated porcelain condenser
JP1985037709A
Control device for starting clutch
JP1989016442A
Resin composition
JP1993005054A